A cross-sectional study of changes in markers of immunological effects and lung health due to exposure to multi-walled carbon nanotubes. Issue 3 (16th March 2017) - Vlaanderen, Jelle; Pronk, Anjoeka; Rothman, Nathaniel; Hildesheim, Allan; Silverman, Debra; Hosgood, H. Dean; Spaan, Suzanne; Kuijpers, Eelco; Godderis, Lode; Hoet, Peter; Lan, Qing; Vermeulen, Roel
Abstract: Background: Multi-wall carbon nanotubes (MWCNTs) are manufactured nanomaterials to which workers and the general population will be increasingly exposed in coming years. Little is known about potential human health effects of exposure to MWCNTs, but effects on the lung and the immune system have been reported in animal and mechanistic studies. Objectives: We conducted a cross-sectional study to assess the association between occupational exposure to MWCNTs and effects on lung health and the immune system. Methods: We assessed 51 immune markers and three pneumoproteins in serum, complete blood cell counts (CBC), fractional exhaled nitric oxide (FENO), and lung function among 22 workers of a MWCNT producing facility and 39 age- and gender-matched, unexposed controls. Measurements were repeated four months later among 16 workers also included in the first phase of the study. Regression analyses were adjusted for potentially confounding parameters age, body mass index, smoking, and sex, and we explored potential confounding by other factors in sensitivity analyses. Results: We observed significant upward trends for immune markers C-C motif ligand 20 ( p  = .005), basic fibroblast growth factor ( p  = .05), and soluble IL-1 receptor II ( p  = .0004) with increasing exposure to MWCNT. These effects were replicated in the second phase of the study and were robust to sensitivity analyses. We also observed differences in FENO and several CBC parameters between exposed and non-exposed, but no difference in lung function or the pneumoproteins. Conclusions: We observed indications of early effects of occupational exposure to MWCNTs on lung health and the immune system.